THE DIGITAL MIND MAPPING ON WRITING SKILLS OF EXPLANATORY TEXTS IN ELEMENTARY SCHOOL - Saskia Azza Nabila; Ermawati Zulikhatin Nuroh (Universitas Islam Negeri Mataram, 2025)
This study examines the effectiveness of digital mind mapping media on explanatory text writing skills. The subjects of this study were 25 sixth-grade students at SDN Sepande. Data collection in this study used quantitative pre-experimental data analysis techniques and data collection methods in pre-tests and post-tests to determine the effectiveness of digital mind mapping. Initial data collection in the form of a pre-test involved participants being directed to write explanatory texts on a predetermined topic, followed by a pre-test using digital mind mapping. The study's results showed an increase in students' writing skills during the study, as indicated by changes in the average scores obtained from the pre-test and post-test. The average score in the pre-test was 57.00, while the average score in the post-test was 82.80. Therefore, it can be concluded that sixth-grade students' explanatory text writing skills at SDN Sepande improved after using digital mind mapping.